2012
DOI: 10.5539/jas.v4n5p83
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Biological Activity in Northern Aspen Parkland Native and Seeded Pasture Using Bait Lamina

Abstract: Many native grasslands in the Aspen Parkland of western Canada have been converted to seeded forages. We used bait lamina to test the hypothesis that this change has altered soil biological activity. Bait lamina removal varied with both vegetation type and soil depth (p=0.03). Bait removal was 31% in the shallow (0-5 cm) soil profile, and similar between native (32%) and seeded (30%) grassland. Although bait removal was lower at 5 to 10 cm depth (23%), removal in native grassland was greater (26%) than in adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The feeding activity of soil fauna in the inorganic fertilizer combined with organic fertilizer polts was high in the 0-6 cm depth range. Many studies show that feeding activities of soil fauna were strongly reduced from 4 to 8 cm soil layer in grassland and forest sites (Larade et al, 2012;Filzek et al, 2004;Gongalsky et al, 2008;Rożen et al, 2010). Other studies showed that soil fauna feeding activities were higher in the bottom of 5-8 cm soil layer than in topsoil layers at ryegrass and soybean fields (Marx et al, 2016;Mousavi et al, 2022).…”
Section: Effect Of Organic Fertilizer Incorporation On Soil Fauna Fee...mentioning
confidence: 99%
“…The feeding activity of soil fauna in the inorganic fertilizer combined with organic fertilizer polts was high in the 0-6 cm depth range. Many studies show that feeding activities of soil fauna were strongly reduced from 4 to 8 cm soil layer in grassland and forest sites (Larade et al, 2012;Filzek et al, 2004;Gongalsky et al, 2008;Rożen et al, 2010). Other studies showed that soil fauna feeding activities were higher in the bottom of 5-8 cm soil layer than in topsoil layers at ryegrass and soybean fields (Marx et al, 2016;Mousavi et al, 2022).…”
Section: Effect Of Organic Fertilizer Incorporation On Soil Fauna Fee...mentioning
confidence: 99%